Preliminary notes on the mammals of the Bontebok National Park - C.T. Stuart; H.H. Braak (Koedoe: African Protected Area Conservation and Science, 1978)
A check-list of the mammals known to occur in the Bontebok National Park, Republic of South Africa, is presented, including general observations.